A Field Survey on Promotion of Safety in School Laboratories (International Journal of Active Learning, 2023)
A training activity was conducted in a technical high school aimed at promoting the health and safety culture in chemistry laboratories. 84 students were involved. Three seminar meetings and three laboratory workshops were held. At the beginning of the activity (T0) and at the end (T1) the following tools were given to the students: a questionnaire on the topics covered by the training activity; a questionnaire containing the general risk propensity scale and some additional questions relating to the perception of risk. A comparison of the data between T0 and T1 revealed an overall improvement in students’ ability to identify specific hazards, but it also highlighted the need to improve the good laboratory practices. Students tend to attribute a greater awareness to themselves than they are willing to acknowledge in their peers. It emerged a more effective promotion of risk-awareness rather than risk-management, as predictable, considering the short intervention time.